(untitled) (Revista Electrónica REDINE, 2019)
The purpose of this article is to present the Design of an Action Plan for the Training of Teachers in the use of the Pilates Method as a Fitness modality for the Psychomotor Development of the Preschooler, due to the lack of experience shown by some teachers regarding the topic of study. Framed in a descriptive field research under the feasible project modality, the survey was used as a technique and as a tool a questionnaire. Reliability was determined by using the Kuder-Richardson method (K-R20). Among the results can be pointed the need for reinforcing the theoretical and practical knowledge about psychomotricity and its elements among teachers as well as the possibility of the use of the Pilates Method as an educational strategy.